Pharmacoresistant Severe Mental Health Disorders in Children and Adolescents: Functional Abnormalities of Cytochrome P450 2D6 - Thümmler, Susanne; Dor, Emmanuelle; David, Renaud; Leali, Graziella; Battista, Michele; David, Alexia; Askenazy, Florence; Verstuyft, Céline (Frontiers in Psychiatry, 2018)
Background: Severe mental health disorders in children and adolescents represent a major public health problem. Despite adequate drug treatment, some patients develop pharmacoresistant disease. As a consequence, physicians are confronted with prescribing challenges, prolonged hospitalization and increased risk of adverse events, thus aggravating short-, medium- and long-term prognosis. The majority of psychotropic treatments, particularly antipsychotics and antidepressants, are metabolized at hepatic level by cytochrome P450 (CYP), particularly by CYP3A4 and CYP2D6. Several CYP2D6 genetic polymorphisms are described to be associated with ultrarapid (UM) or poor drug metabolism (PM), inducing clinical resistance and/or adverse events, and might therefore be related to pharmacoresistant severe mental health disease. Case presentation: A total of 9 pharmacoresistant patients (4 females, 5 males) aged 11 to 16 (mean 14.1) years have been genotyped for CYP2D6 between January, 2015 and April, 2016. Patients were diagnosed with schizophrenia (n=5), autism spectrum disorders (ASD, n=2), intellectual disability with challenging behavior (n=2), oppositional defiant disorder (n=1), and post-traumatic stress and borderline personality disorders (n=1). They had a treatment history with on average 6.1 (3-9) psychotropic, 5 (3-7) antipsychotic and 3.4 (2-5) CYP2D6-metabolized antipsychotic and antidepressant molecules. Five patients (56%) presented functional anomalies of the CYP2D6 gene: 3 patients were UM metabolizers with gene duplication and 2 patients were PM with *4/*41 and *3/*4 polymorphisms. Conclusions: Functional anomalies of CYP2D6 concerned more than half of our paediatric inpatient sample with pharmacoresistant disease. However, our case reports are limited by the low sample size. Nevertheless, knowledge of individual metabolism and in particular CYP2D6 genotyping should be considered for clinical workup and therapy adjustment in resistant patients in child and adolescent psychiatry, and might permit better treatment outcome, increased treatment adherence and diminished adverse events.